2013
DOI: 10.2203/dose-response.13-004.calabrese
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Use of Radiotherapy in the Treatment of Sinus Infections

Abstract: The aim of this paper is to assess the historical role of radiotherapy in the treatment of sinus infections. This assessment involved a literature-based review of how radiotherapy was used to treat sinus infections in the first half of the 20(th) century. Low doses of x-rays were used with considerable success to treat nearly 3,000 patients of sinus infection in a span of 12 years with these cases being reported in leading medical journals as case studies. The mechanism of x-ray induced reduction of inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“… 71 Calabrese and Dhawan also reported on 3000 patients suffering from sinus infections treated successfully, and some involved children. 72 The same authors also reported on the successful treatment of otitis media and cervical lymphadenitis, many being children. 73 The radiation doses employed to treat these diseases ranged from 30-100 roentgen; importantly, no reports of long-term harm has ever been documented to occur from these treatments.…”
Section: Radiophobic Concern #3: Children Are More Susceptible To Radmentioning
confidence: 95%
See 2 more Smart Citations
“… 71 Calabrese and Dhawan also reported on 3000 patients suffering from sinus infections treated successfully, and some involved children. 72 The same authors also reported on the successful treatment of otitis media and cervical lymphadenitis, many being children. 73 The radiation doses employed to treat these diseases ranged from 30-100 roentgen; importantly, no reports of long-term harm has ever been documented to occur from these treatments.…”
Section: Radiophobic Concern #3: Children Are More Susceptible To Radmentioning
confidence: 95%
“…73 The radiation doses employed to treat these diseases ranged from 30-100 roentgen; importantly, no reports of long-term harm has ever been documented to occur from these treatments. 61,[70][71][72][73][74] It should be mentioned that the treatment for cervical lymphadenitis involved nasopharyngeal radium irradiation (NRI) treatment. This was used to shrink lymph tissues in the neck.…”
Section: Radiophobic Concern #2: Radiation Exposures Are Cumulativementioning
confidence: 99%
See 1 more Smart Citation
“…Long before high dose radiotherapy became a standard treatment for cancer, LDRT has been employed to treat benign diseases because of its anti-inflammatory effect. Indeed, LDRT was a popular and effective treatment for a myriad of inflammatory or infectious disease ranging from arthritis to sinusitis, ear infection, and potentially deadly infection such as pneumonia and gas gangrene [23][24][25][26][27][28][29][30]. A single treatment of 20 cGy to 200 cGy has been reported to be effective in inducing fast and lasting effects for those conditions [29].…”
Section: Pathophysiology Of Covid 19 Pneumonitismentioning
confidence: 99%
“…In fact, radiotherapy which delivers radiation doses much higher than X-rays, has been used to successfully treat many human diseases including neurodegenerative and inflammatory conditions, infections, and cancers ( Table 2 ). 44 , 47 - 69 …”
Section: Estimated Theoretical Cumulative Effective Doses Remain Belomentioning
confidence: 99%